(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In this article, we focus on linguistic units that reflect emotions. Within the framework of Kyrgyz literature, we attempted to investigate the lexico-semantic meanings of words, sounds, and basic terms. In a literary work, the same affix can evoke different emotions, and depending on the individual skill of the author in creating a literary image, it can convey various meanings in both grammatical and semantic aspects. In the study of word meanings, it becomes clear that due to the combination of sentence components, the original meaning is lost, and new words emerge that reflect diverse meanings. As a result, emotional expressiveness and poetic rhythm are formed, gaining aesthetic strength. In the work, in the dialogues and monologues of the characters, words are used not only in their literal sense—endearing, insulting, mocking—but also, depending on the tone of sound, they create various emotions.